The Impacts of Trimming Mangroves - Natalia Medina Irizarry; Michael Andreu (EDIS)
Mangroves provide quintessential ecosystem services in Florida, where there are three native mangrove species: red mangrove (Rhizophora mangle), black mangrove (Avicennia germinans), and white mangrove (Laguncularia racemosa). Mangroves extend from the Florida Keys up to peninsular Florida along the coastlines.They are often removed or trimmed to capitalize on coastal views valued by residents and visitors. To protect mangroves and the ecosystem services they provide, the 1996 Mangrove Trimming and Preservation Act provides management guidance. A literature review about trimming mangroves uncovered that not all species remain healthy after trimming. To minimize the negative impacts of trimming, landowners should carefully consider the amount of biomass removed, trimming frequency and timing, and best trimming techniques for the mangrove species they are managing.